ŚWIADOMOŚĆ UNORMOWANA. TOŻSAMOŚĆ NARODOWA I TOŻSAMOŚĆ EUROPEJSKA JAKO PRZEDMIOT PRAWA UE - Muszyński, Mariusz (Zeszyty Prawnicze, 2017)
Standardized Awareness. National and European Identity as a Matter of the European Union Law Summary Since the very beginning of the European integration process, the national identity has constituted a problematic issue for the integration as such. The main question was, whether the national identity is an opportunity or an obstacle to the European Union. The national identity constitutes collective awareness – comprising such elements as “material culture” (history, literature, arts, music, folklore), language, spiritual culture (customs, public morality, religion) and legal culture. Initially, the European Union welcomed these distinguished characteristics. The European Union founders believed that for its durability the community needs not only an open economic area but also social diversity. Hence, the Maastricht Treaty establishing the European Union includes an article guaranteeing the national identity of the European Union member states. The obligation to respect the national identity is associated with instruments that are left to the disposal of the member states. In this respect, two groups of treaty provisions are to be distinguished. Some of the existing treaty provisions require that the European Community operate to preserve the national identity (to stimulate, to support and to supplement the member states activities in the field of propagation of culture and history, preservation of national heritage and in non-commercial exchange of literary and art works). Other treaty provisions block Brussels’ (the European Union’s organs) actions against those member states which for the purpose of preserving national identity, infringe the regulations of the European Community. In the Amsterdam Treaty of 1997, its authors introduced a system reconstruction of the ideological foundations of the European Union. Although the national identity has not been replaced with the supranational identity, the new axiological fundament of the united Europe was defined. It should be stressed that the Amsterdam Treaty created so called “European identity” existing parallel to the national identity One of the treaty goals is to transform the national-particularistic way of thinking about the European Union citizens into the “European awareness”. The European Union is obliged not only to support the State Parties’ culture but also to display all of the axiological elements that are common for the entire European continent. Hence, national identity as a sociological value is no more autonomic. The European Union started to create a substrate of the European culture that has gone beyond the simple sum of national’s cultures, which would be the basis for the future European statehood. What remains unanswered is whether the European identity created in such a way poses a threat to the national ties or not. National and European identities are autonomous institutions only on the surface. European standards of human rights protection go far beyond political and economic rights. These standards interfere in customs and traditions and in public morality of nations, trying to find a balance between them. In reality, the danger of such a process is correlated with the nature of the economic integration as well. In the process of creation of the law of the European Union , economic issues are treated with priority. Hence, free trade undermines the protection of works of art, open borders create favourable conditions for the transfer of pornography as well as the trend to re-define the history. Therefore, the authors of the treaties have created a “safety valve” – all of the aforementioned norms which constitute legal instruments of protection of the national values. Hence, the problem consists in their proper use by the member states.